Genetic characterization studies of F population of Indian mustard × East- 2 European mustard through principal component analysis (Journal of Oilseed Brassica, 2026)
The study was conducted during the Rabi season of 2019-20, focused on the principal component analysis (PCA) of F 2 generation resulting from a cross between Indian mustard and East European mustard. The F population, comprising 2 359 plants, was systematically evaluated for agromorphological traits, and PCA revealed three principal component axes, collectively explaining 71.45% of the total variation. Notably, the first component (PC1) primarily featured plant morphological and seed yield-contributing traits, contributing maximum variability (42.70%) while PC2 contributed for 14.43% of total variability and PC3 14.32% of total variability. Additionally, subsequent principal components highlighted specific trait contributions, demonstrating the potential for effective selection in crop breeding programs. The study underscores the importance of employing PCA to evaluate genetic diversity and discerns the prime contributors to variability in Indian mustard, providing valuable insights for crop breeding programs.